2005
DOI: 10.1007/s10722-004-6146-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Developmental Stages Length on Yield and some Quality Traits of Turkish Durum Wheat (Triticum turgidum L. Convar. durum (Desf.) Mackey) Landraces: Influence of Developmental Stages Length on Yield and Quality of Durum Wheat

Abstract: Effect of developmental stages length on yield and some quality traits of Turkish durum wheat (Triticum turgidum L. convar. durum (Desf.) Mackey) landraces: influence of developmental stages length on yield and quality of durum wheat AbstractThe study aimed at exploring durum wheat landraces to be utilized in breeding programs. 566 single durum wheat plants selected from 117 populations collected from 12 provinces were studied. The selected material was planted for characterizing their some qualitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The panel of 53 landraces has a significant lower level of genetic diversity than the panel of 97 durum wheat cultivars. But previous research showed that landraces had wide genetic diversity, while the cultivars had narrow genetic diversity due to high selection pressure and genetic drift in breeding programs [20,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…The panel of 53 landraces has a significant lower level of genetic diversity than the panel of 97 durum wheat cultivars. But previous research showed that landraces had wide genetic diversity, while the cultivars had narrow genetic diversity due to high selection pressure and genetic drift in breeding programs [20,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…A higher protein content and quality without the need for late-season nitrogen inputs are therefore major breeding objectives. However new varieties should be particularly suitable for whole-meal bread making and artisan baking processes, combining sensory and nutritional qualities (e.g., increased micro-nutrients) as the consumers of organic bread expect highest organoleptic quality (Zencirci and Karagoz, 2005). Farm households allocate resources for production of favorite or preferred landraces, expecting benefits to accrue from their subsequent consumption or sale in local markets (Brush and Meng, 1998).…”
Section: Origin Of Wheat Landracesmentioning
confidence: 99%
“…Therefore, direct use values, particularly the quality traits that farmers consider as valuable for consumption are indicators of private value. Socio-cultural values motivate farmers to retain some preferred landraces on the farm, and they appreciate the special organoleptic qualities and multiple uses of these landraces, despite the availability of improved wheat varieties in their locality (Zencirci and Karagoz, 2005). Landraces, especially those having multiple home uses, are more likely to be maintained for the foreseeable future.…”
Section: Origin Of Wheat Landracesmentioning
confidence: 99%
See 1 more Smart Citation
“…Einkorn (Triticum monococcum spp. monococcum), the wheat ancestor, which has resistance to cold, drought, and salinity stress (Karagöz and Zencirci, 2005;Zencirci and Karagöz, 2005;Aslan et al, 2016a;Aslan et al, 2016b;Arzani and Ashraf, 2017) is considered possibly a good genetic resource against these stresses. Selecting a well-designed single or multi drought-resistant trait(s) from these resources and to incorporate into high yielding wheat genotypes seems feasible today (Braun et al, 1998;Merah, 2001).…”
Section: Introductionmentioning
confidence: 99%